If the value of
4
0
4
C
4
−
4
C
1
3
0
3
C
4
+
4
C
2
2
0
2
C
4
−
4
C
3
1
0
1
C
4
can be represented as
1
0
1
α
. The value of
α
is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@aryan goyat @Rishabh Deep Singh can you tell me how you did it pl. ?
I just wrote a solution can you please check it?
Log in to reply
thank you -thank you , aap bahut ache hai sir :)
Log in to reply
Bhai i am not Sir i am a student, Tag me if you need any help.
Log in to reply
@Rishabh Deep Singh – yes bhai , i will be sure to do it :) thnx again :)
@Rishabh Deep Singh – bhai, can you give me some help regarding NDa exam ? i'll be giving it this year :) how to score high in it ?
Log in to reply
@Hiroto Kun – i dont Know much about NDA but it is easy and you have to practice for the physical test which is the real challenge. Otherwise the written test is not soo hard.
Log in to reply
@Rishabh Deep Singh – oh , yeah i think i'll pass the written one :)
@Keshav Tiwari plz reply
Log in to reply
Sorry , but i won't we able to post a solution this week . I will surely do so next week . : )
Log in to reply
Ok i will remind u after sunday
Problem Loading...
Note Loading...
Set Loading...
The Given equation can be re written as
S = ∑ r = 0 n − 1 ( − 1 ) r n C r k ( n − r ) C n for n = 4 and k = 1 0 1
Consider ( 1 + x ) n = ∑ r = 0 n n C r x r
replace x By − ( 1 + x ) k and re writing the equation as
( ( 1 + x ) k − 1 ) n = ∑ r = 0 n ( − 1 ) n − r ( n C r ) ( 1 + x ) k ( n − r )
Now Comparing coefficient of x n in both sides ∀ ( n − r ) > 0 The R . H . S . Gives us S
For L . H . S . differentiate it n times and dividing by n ! then put x = 0 and we will get S = ( k ) n
= > S = ∑ r = 0 n − 1 ( − 1 ) ( n − r ) ( n C r ) ( k ( n − r ) C n ) = ( k ) n
Now in Our Case n = 4 and k = 1 0 1
S = ∑ r = 0 3 ( − 1 ) ( 4 − r ) ( 4 C r ) ( 1 0 1 ( 4 − r ) C 4 )
( ( 1 + x ) 1 0 1 − 1 ) 4 = ( ( 1 − ( 1 + x ) 1 0 1 ) 4 = ( 4 C 0 ) ( − ( 1 + x ) 1 0 1 ) 0 + ( 4 C 1 ) ( − ( 1 + x ) 1 0 1 ) 1 + ( 4 C 2 ) ( − ( 1 + x ) 1 0 1 ) 2 + ( 4 C 3 ) ( − ( 1 + x ) 1 0 1 ) 3 + ( 4 C 4 ) ( − ( 1 + x ) 1 0 1 ) 4
Now comparing coefficients of x 4 in Both Sides.
R . H . S . gives us S and For L . H . S . we have to compute 4 ! f ( 4 ) ( 0 ) which is 4 t h derivative of f ( x ) = ( ( 1 + x ) 1 0 1 − 1 ) 4 divided by 4 !
f 1 ( x ) = 4 0 4 ( x + 1 ) 1 0 0 ( ( 1 + x ) 1 0 1 − 1 ) ) 3
f 2 ( x ) = 4 0 4 0 0 ( x + 1 ) 9 9 ( ( 1 + x ) 1 0 1 − 1 ) ) 3 + 1 2 2 4 1 2 ( x + 1 ) 2 0 0 ( ( 1 + x ) 1 0 1 − 1 ) ) 2
f 3 ( x ) = 3 9 9 9 6 0 0 ( x + 1 ) 9 8 ( ( 1 + x ) 1 0 1 − 1 ) ) 3 + 3 6 7 2 3 6 0 0 ( x + 1 ) 1 9 9 ( ( 1 + x ) 1 0 1 − 1 ) ) 2 + 2 4 7 2 7 2 2 4 ( x + 1 ) 3 0 0 ( ( 1 + x ) 1 0 1 − 1 ) ) 1
f 4 ( x ) = 3 9 1 9 6 0 8 0 0 ( x + 1 ) 9 7 ( ( 1 + x ) 1 0 1 − 1 ) ) 3 + 8 5 1 9 8 7 5 2 0 0 ( x + 1 ) 1 9 8 ( ( 1 + x ) 1 0 1 − 1 ) ) 2 + 1 4 8 3 6 3 3 4 4 0 0 ( x + 1 ) 2 9 9 ( ( 1 + x ) 1 0 1 − 1 ) ) 1 + 2 4 9 7 4 4 9 6 2 4 ( x + 1 ) 4 0 0
f 4 ( 0 ) = 2 4 9 7 4 4 9 6 2 4
Now coefficient of x 4 in f ( x ) is 4 ! f 4 ( 0 ) = 4 ! 2 4 9 7 4 4 9 6 2 4 = 1 0 4 0 6 0 4 0 1 = 1 0 1 4